Synthesis of 3d Transition Metal Oxides and Correlation of their Electrical and catalytic Properties in Decomposition of Hydrogen Peroxide - B. Meher, Chetan; P. Tandel, Suhas; P. Malve, Sheela; Varadrajan, Anand (Asian Journal of Chemistry, 2010)
Catalytic decomposition of hydrogen peroxide has been carried outemploying some 3d transition metal oxides, synthesised mostly by theprecipitation technique. Kinetic and thermodynamic activation energieshave been calculated, making use of the Arrhenius plots in the latter case.The Seebeck coefficient measurement is used for the determination of thenature of charge carriers. An attempt has been made to correlate the thermodynamicand electronic activation energies of the synthesised oxides,calculated for the catalytic decomposition of hydrogen peroxide. It hasbeen found that the electronic activation energy plays an important role inunderstanding the catalytic activity of these transition metal oxides.